2016
DOI: 10.1080/07391102.2015.1133321
|View full text |Cite
|
Sign up to set email alerts
|

Probing the interaction between cHAVc3 peptide and the EC1 domain of E-cadherin using NMR and molecular dynamics simulations

Abstract: The goal of this work is to probe the interaction between cyclic cHAVc3 peptide and the EC1 domain of human E-cadherin protein. Cyclic cHAVc3 peptide (cyclo(1,6)Ac-CSHAVC-NH2) binds to the EC1 domain as shown by chemical shift perturbations in the 2D 1H,-15N-HSQC NMR spectrum. The molecular dynamics (MD) simulations of the EC1 domain showed folding of the C-terminal tail region into the main head region of the EC1 domain. For cHAVc3 peptide, replica exchange molecular dynamics (REMD) simulations generated five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…, ADTC5, HAV6, and cHAVc3). These cadherin peptides caused changes in chemical shifts of several amino acids on the EC1 as observed using heteronuclear single quantum correlation (HSQC) NMR spectroscopy experiments 33 . A combination of NMR spectroscopy and molecular docking experiments indicated that HAV6 and cHAVc3 peptides have a different binding site than that of ADTC5 peptide.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…, ADTC5, HAV6, and cHAVc3). These cadherin peptides caused changes in chemical shifts of several amino acids on the EC1 as observed using heteronuclear single quantum correlation (HSQC) NMR spectroscopy experiments 33 . A combination of NMR spectroscopy and molecular docking experiments indicated that HAV6 and cHAVc3 peptides have a different binding site than that of ADTC5 peptide.…”
Section: Discussionmentioning
confidence: 92%
“…The hypothesis for the mechanism of action of cadherin peptides is that they bind in equilibrium fashion to the extracellular domain of E-cadherins to inhibit E-cadherin homophilic physical interactions ( i.e. , trans and/or cis interactions) among cadherins in the intercellular junctions in an equilibrium fashion 33 . The physical nature of this inhibition is not expected to change the expression of E-cadherin on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Pengobatan penyakit yang menyerang otak merupakan penyakit yang sulit dilakukan karena penghantaran molekul obat menuju ke otak sangat sulit [1]. Hal ini disebabkan karena adanya penghalang biologis yaitu blood-brain barrier (BBB) [2].…”
Section: Pendahuluanunclassified
“…Alaofi dkk. [1] menginteraksikan peptida cHAVc3 dengan E-kadherin domain EC1 dan hasilnya menunjukkan bahwa peptida cHAVc3 mampu meningkatkan porositas juntion antar sel [1]. Selain turunan peptida kadherin seperti peptida ADTC1, ADTC5, dan ADTC6, terdapat turunan ADT6 yang belum dilakukan penelitian secara eksperimen maupun komputasi yaitu peptida ADTC3.…”
Section: Pendahuluanunclassified
“…This interaction study has been studied computationally using the molecular docking method between cadherin peptides against EC1 and EC5 domains [2][3][4][5]. The cadherin peptide is a derivative synthesis peptide of the bulge and groove region sequences in the cadherin, where the bulge region is an ADT structure and the groove region is a HAV structure [6].…”
Section: Introductionmentioning
confidence: 99%